Mentoring and support system for new teacher development program - Norasmah Othman, Aney Marinda Muhammad Amin, (Opción, 2019)
This study aimed to identify the level of mentoring and support system in the implementation of NTDP and its differences based on school level. The survey design was selected and questionnaire was used as the research instrument. The results showed that the level of mentoring in NTDP was very high and the level of support system was high. In conclusion, the cooperation and commitment of school community in providing various forms of support and guidance can ensure that NTDP is implemented successfully.